The development of a surface acoustic wave strain sensor - Donohoe, Brian (Trinity College (Dublin, Ireland). Department of Mechanical and Manufacturing Engineering, 2011)
Multi sensors networks are becoming increasingly prevalent in modern engineering applications. In multi sensor networks, wireless sensors are preferred over traditional wired methods. Sensors based upon the surface acoustic wave resonators (SAWR) are often identified as a potential candidate to act as wireless and passive strain sensors. This thesis details the design, fabrication, modelling, calibration and packaging of SAW strain sensors as a general purpose modular strain sensor. The motivation of this work is to develop an understanding of the practical implementation of SAWR strain sensors for real world applications. Through collaboration with an industrial organisation a SAWR strain sensor suitable for wireless sensing was integrated into a commercial wireless SAWR temperature interrogation platform. The sensors were then calibrated through a modified version of the American standard test methods for performance characterisitics of bonded resistance strain gages, for a range of temperatures and loading conditions. Experimental results were correlated against existing modelling techniques using a novel method for the validation of SAWR strain sensors. Over the course of the work a range of adhesive were tested to provide a rigorous assessment of SAWR as strain sensors. The prototype bare die sensors were then packaged to form a modular SAWR strain sensor. This thesis provides an in-depth discussion on the development of SAWR as strain sensors, it is hoped that the approach taken within will aid future work in the development of a SAWR strain sensor.
Keywords: Mechanical and Manufacturing Engineering, Ph.D.; Ph.D. Trinity College Dublin